Kinesiophobia and Related Factors in Patients with Osteoporosis and Osteopenia - Elbasti, Muhammet Sahin; Yentur, Songul Baglan (Galenos Publ House, 2024)
Objective: This study aimed to determine the relationship between kinesiophobia, physical activity level (PAL), and quality of life (QoL) in patients with osteoporosis (OP) and osteopenia (OPN). Materials and Methods: The study included 41 patients with OP and 41 with OPN. Kinesiophobia was assessed using the Tampa scale of Kinesiophobia, PAL using the International Physical Activity Questionnaire-Short Form, and QoL using the European Osteoporosis Federation QoL questionnaire. Results: The study was completed with 80 patients (40 patients in each group. Although there was a significant difference between the two groups in kinesiophobia (p=0.027), no significant difference was observed in terms of activity levels (p=0.103). In addition, a significant correlation was observed between kinesiophobia and PAL and all sub-parameters of QoL in patients with OP (p<0.05). A significant correlation was observed between kinesiophobia and PAL in patients with OPN (p<0.001, r=-0.544) however no significant correlation was observed between kinesiophobia and QoL (p>0.05). Conclusion: Kinesiophobia was found to be high in patients with OP and OPN, which negatively affected the PAL and QoL of patients with OP. Considering the positive effects of exercise on these patients, the evaluation and treatment of kinesiophobia have become increasingly important.
Osteoporoz ve Osteopeni Hastalarında Kinezyofobi ve İlişkili Faktörler
Keywords: Kinesiophobia; physical activity level; quality of life; osteoporosis; osteopenia